EVALUATION OF PHARMACOECONOMIC DIRECT COST IN DIABETES PATIENTS - Sangam, Kamala; ANIFA, MOHAMMED; K, Swathi; K, VENKATESWARLU; REDDY T, RAM MOHAN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Â Diabetes Mellitus (DM) is a major cause of disability, morbidity and mortality Worldwide. The objective of this study is to evaluate the Pharmacoeconomic direct health care cost in type II Diabetes with complications and Diabetes alone: A cost of illness study. Methods: Â A Prospective observational study was conducted for one year at the Care diabetes Center; Warangal. The enrolled patients were followed and the information collected contains: total direct costs, which include direct medical costs and direct nonmedical cost. The data observed was analyzed for the average cost incurred in treating the diabetic patient. Results:Â The total average costs per diabetic patient without complications was Rs. 8695.7Â±1341,Â this includes the average direct medical cost Rs. 6366.50Â± 561.12, the average lab cost Rs. 1368.84Â±64.8, the average direct non Medical Cost was Rs. 960.36Â±14.04 compared toÂ those with DM complications,the total average cost was Rs. 12960.73Â±549.96 for macro vascular complications, Rs. 11039.11Â±265.36 for micro vascular complications. To treat Diabetes with comorbidities which include both micro and macro complications the total average cost was Â Rs. 16658.13Â±1393.44, the average direct medical cost was Rs. 14071.77Â±2884.68, the average lab cost Rs. 1628.04Â±51, the average direct non Medical Cost was Rs.958.32Â±13.08. The costs were found to increase progressively with the increase in the number of complications. Costs also differed significantly across the types of complications. Conclusion: Our study concludes that the cost of Diabetes with complications resulted about 2 times higher than compared to Diabetes alone. Key words: Â Cost analysis; diabetes; economics; health care; direct medical cost; non medical cost